`(dy)/dx = 3x^2/y^2`

This differential equation is separable since it can be rewritten in the form

`N(y)dy = M(x) dx`

So separating the variables, the equation becomes

`y^2dy = 3x^2dx`

Taking the integral of both sides, the equation becomes

`int y^2dy = int3x^2dx`

`y^3/3 + C_1 = 3*x^3/3 + C_2`

`y^3/3 + C_1 = x^3 + C_2`

Since C1 and C2 represent any number, it can be expressed as a single constant C.

`y^3/3 = x^3 + C`

**Therefore, the general solution of the given `y^3/3 = x^3 + C`
.**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.